Diagnostic yield of high-resolution manometry with a solid test meal for clinically relevant, symptomatic oesophageal motility disorders: serial diagnostic study. (September 2017) - Ang, Daphne; Misselwitz, Benjamin; Hollenstein, Michael; Knowles, Kevin; Wright, Jeff; Tucker, Emily; Sweis, Rami; Fox, Mark
Summary: Background: The use of high-resolution manometry (HRM) to diagnose oesophageal motility disorders is based on ten single water swallows (SWS); however, this approach might not be representative of oesophageal function during the ingestion of normal food. We tested whether inclusion of a standardised solid test meal (STM) to HRM studies increases test sensitivity for major motility disorders. Additionally, we assessed the frequency and cause of patient symptoms during STM. Methods: Consecutive patients who were referred for investigation of oesophageal symptoms were recruited at Nottingham University Hospitals (Nottingham, UK) in the development study and at University Hospital Zürich (Zürich, Switzerland) in the validation study. HRM was done in the upright, seated position with a solid-state assembly. During HRM, patients ingested ten SWS, followed by a standardised 200 g STM. Diagnosis of oesophageal motility disorders was based on the Chicago Classification validated for SWS (CCv3) and with STM (CC-S), respectively. These studies are registered withClinicalTrials.gov, numbersNCT02407938 andNCT02397616 . Findings: The development cohort included 750 patients of whom 360 (48%) had dysphagia and 390 (52%) had reflux or other symptoms. The validation cohort consisted of 221 patients, including 98 (44%) with dysphagia and 123 (56%) with reflux symptoms. More patients were diagnosed with a major motility disorder by use of an STM than with SWS in the development set (321 [43%] patients diagnosed via STM vs 163 [22%] via SWS; p<0·0001) and validation set (73 [33%] vs 49 [22%]; p=0·014). The increase was most evident in patients with dysphagia (241 [67%] of 360 patients on STM vs 125 [35%] patients on SWS in the development set, p<0·0001), but was also present in those referred with reflux symptoms (64 [19%] of 329 patients vs 32 [10%] patients in the development set, p=0·00060). Reproduction of symptoms was reported by nine (1%) of 750 patients during SWS and 461 (61%) during STM (p<0·0001). 265 (83%) of 321 patients with major motility disorders and 107 (70%) of 152 patients with minor motility disorders reported symptoms during the STM (p=0·0038), compared with 89 (32%) of 277 patients with normal motility as defined with CC-S (p<0·0001). Interpretation: The diagnostic sensitivity of HRM for major motility disorders is increased with use of the STM compared with SWS, especially in patients with dysphagia. Observations made during STM can establish motility disorders as the cause of oesophageal symptoms. Funding: None.